APOL1 Kidney Risk Variants and Proteomics. Issue 5 (May 2022) - Chen, Teresa K.; Surapaneni, Aditya L.; Arking, Dan E.; Ballantyne, Christie M.; Boerwinkle, Eric; Chen, Jingsha; Coresh, Josef; Köttgen, Anna; Susztak, Katalin; Tin, Adrienne; Yu, Bing; Grams, Morgan E.
Visual Abstract: Abstract : Background and objectives: The APOL1 risk variants (G1 and G2) are associated with kidney disease among Black adults, but the clinical presentation is heterogeneous. In mouse models and cell systems, increased gene expression of G1 and G2 confers cytotoxicity. How APOL1 risk variants relate to the circulating proteome warrants further investigation. Design, setting, participants, & measurements: Among 461 African American Study of Kidney Disease and Hypertension (AASK) participants (mean age: 54 years; 41% women; mean GFR: 46 ml/min per 1.73 m 2 ), we evaluated associations of APOL1 risk variants with 6790 serum proteins (measured via SOMAscan) using linear regression models. Covariates included age, sex, percentage of European ancestry, and protein principal components 1–5. Associated proteins were then evaluated as mediators of APOL1 -associated risk for kidney failure. Findings were replicated among 875 Atherosclerosis Risk in Communities (ARIC) study Black participants (mean age: 75 years; 66% women; mean eGFR: 67 ml/min per 1.73 m 2 ). Results: In the AASK study, having two (versus zero or one) APOL1 risk alleles was associated with lower serum levels of APOL1 ( P =3.11E-13; P =3.12E-06 [two aptamers]), APOL2 ( P= 1.45E-10), CLSTN2 ( P =2.66E-06), MMP-2 ( P =2.96E-06), SPOCK2 ( P =2.57E-05), and TIMP-2 ( P =2.98E-05) proteins. In the ARIC study, APOL1 risk alleles were associated with APOL1 ( P =1.28E-11); MMP-2 ( P =0.004) and TIMP-2 ( P =0.007) were associated only in an additive model, and APOL2 was not available. APOL1 high-risk status was associated with a 1.6-fold greater risk of kidney failure in the AASK study; none of the identified proteins mediated this association. APOL1 protein levels were not associated with kidney failure in either cohort. Conclusions: APOL1 risk variants were strongly associated with lower circulating levels of APOL1 and other proteins, but none mediated the APOL1 -associated risk for kidney failure. APOL1 protein level was also not associated with kidney failure.